Genetic markers involved in neuroinflammation in Down syndrome: a systematic review - Marina Nascimento Silva; Mariana Dias Lula; Lucas Reis Felício; Bárbara Santos; Lívia Silva Nassif; Marcus Carvalho Borin; Juliana Alvares-Teodoro; Francisco de Assis Acurcio; Augusto Afonso Guerra Júnior (Dementia & Neuropsychologia)
ABSTRACT The immune system plays a fundamental role in protecting human body organs and tissues; however, when exacerbated, it can contribute to the pathology of various conditions. In the central nervous system, immune cell activation, or neuroinflammation, is a key factor in several neurodegenerative diseases. In Down syndrome (DS), the additional copy of chromosome 21 alters gene expression, potentially enhancing inflammatory processes such as neuroinflammation. Therefore, understanding the genetic factors influencing neuroinflammation in DS is essential for identifying biomarkers and therapeutic targets. Objective Identify genetic markers involved in neuroinflammatory processes in individuals with DS. Methods A comprehensive search was conducted in Medical Literature Analysis and Retrieval System Online (Medline) (United States National Library of Medicine [PubMed]), Embase, Cochrane Library, and Latin American and Caribbean Health Sciences Literature (LILACS) databases, and identified ten relevant studies. These studies assessed and compared gene expression between groups with and without DS associated with neuroinflammation. Results Sixty–three genes and 42 genetic markers associated with neuroinflammation in DS were identified. These genes exhibited expression variations that alter inflammatory responses, suggesting a possible link to the progression of neurodegenerative diseases in this population. Conclusions The findings highlight the role of neuroinflammation in neurodegenerative disorders in individuals with DS, especially Alzheimer’s disease. Some studies indicated that the triplicated genes SOD1, APP, S100B, TREM2, IFNR1, and IFNR2 are directly related to neuroinflammation. Additionally, elevated levels of pro-inflammatory cytokines, such as IL–1, IL–6, IL–10, IFNγ, and TNF-α, and complement proteins like C1q, C3, and C9 suggest an exacerbated activation of the immune response. However, the roles these genes may play in neurodegenerative diseases and in increasing or reducing neuroinflammation remain controversial.